Community-based Approach to Sustain Batik Tourism Village Area in the Special Region of Yogyakarta (The Case of Giriloyo Village) - Anggarani Pribudi Anggarani Pribudi (Journal of Social Science, 2020)
The study aims to identify the implementation of Community-based Tourism to sustain Giriloyo Batik Tourism Village as a sustainable tourism destination. The identification analysis of the Community-based approach is based on thirteen fundamental factors of the ideal Community-based Tourism developed and adopted from related existing literature. This study is a qualitative study with an in-depth interview and a thematic analysis method. The results of the study showed that tourism development began after Yogyakarta’s earthquake through supports from NGOs and the Government. Community-based Tourism is implemented which has the characteristics of the thirteen factors of the ideal model of Community-based Tourism I identified. However, there is a difference between the ideal and the fact. The most remarkable gap is in community participation, which in Giriloyo is limited and very active within the Batik Association led by the core members. Stakeholders’ roles are crucial in enabling tourism to flourish in Giriloyo Village. The primary stakeholders are Village Government, Local and Regional Tourism Offices Department, and NGOs. Community-based Tourism has positive impacts, mainly in terms of socio-cultural, economic, and environment. Despite the positive impacts, the community is still struggling with several issues, such as regeneration within the organization, domestic waste management, and product innovation. Concrete efforts are needed to ensure the sustainability of Giriloyo Batik Tourism Village in the long-term.